2016
DOI: 10.1007/s10654-016-0201-3
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin (hCG) concentrations during the late first trimester are associated with fetal growth in a fetal sex-specific manner

Abstract: Human chorionic gonadotropin (hCG) is a pregnancy-specific hormone that regulates placental development. hCG concentrations vary widely throughout gestation and differ based on fetal sex. Abnormal hCG concentrations are associated with adverse pregnancy outcomes including fetal growth restriction. We studied the association of hCG concentrations with fetal growth and birth weight. In addition, we investigated effect modification by gestational age of hCG measurement and fetal sex. Total serum hCG (median 14.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…This might be explained by a potentially greater susceptibility of male fetuses to the impact of hCG variation, or by fetal‐sex‐specific differences in the variation of hCG isoforms. The hypothesis of fetal‐sex‐specific differences is further supported by our previous study that showed that the association of low hCG with lower fetal growth is stronger in pregnancies with a male fetus.…”
Section: Discussionmentioning
confidence: 64%
“…This might be explained by a potentially greater susceptibility of male fetuses to the impact of hCG variation, or by fetal‐sex‐specific differences in the variation of hCG isoforms. The hypothesis of fetal‐sex‐specific differences is further supported by our previous study that showed that the association of low hCG with lower fetal growth is stronger in pregnancies with a male fetus.…”
Section: Discussionmentioning
confidence: 64%
“…Human chorionic gonadotropin (hCG) is a pregnancy- specific hormone that regulates placental development and is produced by trophoblast cells from the time of embryo implantation onwards [21,22]. The determination of hCG, produced exclusively during pregnancy also allows the interpretation of the presence of abnormal pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous epidemiological studies have found that NVP is more common when gestating a female fetus [ 51 53 ], and this finding was replicated in the current study. Several studies have also reported that maternal experience of NVP [ 53 ] and increased hCG concentrations during pregnancy [ 54 ] influence growth rates in female but not male fetuses. The mechanisms by which biological sex may impart vulnerability or protection on the fetal nervous system remain largely unknown [ 55 ].…”
Section: Discussionmentioning
confidence: 99%